Influence of Sex on Gestational Complications, Fetal-to-Neonatal Transition, and Postnatal Adaptation - Lorente-Pozo, Sheila; Parra-Llorca, Anna; Torres, Begoña; Torres-Cuevas, Isabel; Nuñez-Ramiro, Antonio; Cernada, María; García-Robles, Ana; Vento, Maximo (Frontiers in Pediatrics, 2018)
Fetal sex is associated with striking differences during in utero development, fetal to neonatal transition and postnatal morbidity and mortality. Male sex fetuses are apparently protected while in utero resulting in a higher secondary sex rate for males than for females. However, during fetal to neonatal transition and thereafter in the newborn period female exhibit a greater degree of maturation that translates into a better capacity to stabilize, less incidence of prematurity and prematurity-associated morbidities and better long-term outcomes. The present review addresses the influence of sex upon gestation and postnatal adaptation that imply establishment of an adult-type circulation, initiation of breathing, and endurance when confronted with perinatal hypoxia ischemia. There is yet no explanation for the profound mechanisms explaining these differences remain elusive thus further experimental and clinical research are stringently needed.